LA SACRALIZACIÓN DEL TIEMPO EN PRUDENCIO - Guerrero Fuster, Antonio (Antigüedad y Cristianismo, 1995)
Vision and analysis axiological of the consecration of Time in the ambitus of the middle course of the Ebro river during the Later Roman Empire, based on the highly esteemed Cathamerinon of Pmdence. The texts from the Cathamerinon reveal a «new epoch», a promised period of cultural metamorphosis and of a new historical era: the Christian Era, the Era of the Church and of God's people. Pmdence intreprets the period as being a time of Realization (fulfilment) and of Christian catharsis, a time of redention and arrival, in a given historical moment. (...)